A study on English politeness strategies for refusals with reference to Vietnamese equivalents / Phạm Thu Trang; NHDKH Assoc. Prof. Dr. Lê Văn Thanh - Phạm, Thu Trang
The major aim of the study is to identify and explain the choice of politeness strategies for refusals in English and Vietnamese in terms of cross cultural interactions. In addition, the second aim is to contribute some suggestions in teaching and learning English as the second language. The study was completed by several means of main methods: Analytic and synthetic method, descriptive and statistic method, contrastive method. This thesis has contributed some research results: Firstly, although the English and Vietnamese tended to make similar choices in using the most preferred strategies, they displayed two opposing trends in using the number of strategies to refuse the people in different relative power and social distance. The English used more strategies to refuse to same relative power and social distance people than to opposite relative power and social distance ones. The reverse result was found for the Vietnamese; the greater number of strategies was used to refuse opposite relative power and social distance people instead of same relative power and social distance ones. Secondly, it is admitted that English were likely to be more direct than the Vietnamese. Finally, the distinction in the degree of directness between male and female English as not as great as between male and female Vietnamese. In other words, Vietnamese was strongly influenced by the relative power and social distance.